Molecular Genetics of Renal Cell Tumors: A Practical Diagnostic Approach - Alaghehbandan, Reza; Perez Montiel, Delia; Luis, Ana Silvia; Hes, Ondrej (Cancers, 2019)
Renal epithelial cell tumors are composed of a heterogeneous group of tumors with variable morphologic, immunohistochemical, and molecular features. A "histo-molecular" approach is now an integral part of defining renal tumors, aiming to be clinically and therapeutically pertinent. Most renal epithelial tumors including the new and emerging entities have distinct molecular and genetic features which can be detected using various methods. Most renal epithelial tumors can be diagnosed easily based on pure histologic findings with or without immunohistochemical examination. Furthermore, molecular-genetic testing can be utilized to assist in arriving at an accurate diagnosis. In this review, we presented the most current knowledge concerning molecular-genetic aspects of renal epithelial neoplasms, which potentially can be used in daily diagnostic practice.